ANALYSIS OF FACTORS INFLUENCING TRAFFIC SAFETY ON MOUNTAIN ROADS - Ilkhomjon Nosirjonov; Fayzullayev Erkin Zikrullayevich (European Science Publishing, 2024)
This article addresses the critical need to enhance vehicle traffic safety on mountain roads during hazardous conditions, with a focus on the Kamchik Pass as a case study. The research highlights the urgency and relevance of improving traffic safety in mountainous terrains, where unique challenges such as steep gradients, sharp curves, and weather variability significantly increase the risk of accidents. The scientific novelty of this study lies in its approach to analyzing and proposing methods to improve traffic safety under these conditions. Key findings emphasize the importance of targeted interventions and their practical implications for reducing accident rates and ensuring safer travel. The research also underscores the scientific and practical value of implementing safety measures tailored to the specific characteristics of mountain roads.
Keywords: Mountain roads, traffic safety, Kamchik Pass, vehicle movement, accident prevention, road safety analysis, transportation safety, infrastructure improvement, traffic flow management, road safety measures.